The judicial application of human rights law: National, regional and international jurisprudence - Jayawickrama, Nihal (Cambridge University, 2013)
Jayawickrama explores the judicial interpretation of human rights law, incorporating case law from over eighty countries, and the UN, European, and Inter-American human rights monitoring systems. A definitive compendium essential for legal practitioners, government and non-governmental officials, academics and students of constitutional law and the international law of human rights.